A Case Series of Resolving Vitreous Haemorrhage in the Setting of Diabetic Retinopathy - Y. Tiu Ronald; B. Iguban Eleonore; H. Arroyo Milagros (Journal of Ophthalmic Science, 2019)
This case series presents 2 patients (67 and 58 year old females) with resolving vitreous hemorrhage in the setting of diabetic retinopathy. Both patients had around 50% of the retina still visible and the hemorrhage was confined at the posterior vitreous cavity near the retina, hence, a partial pan retinal photocoagulation (PRP) was feasibly applied. On B-scan, both cases showed a liquified vitreous with posterior vitreous detachment (PVD). For both patients, vitreous hemorrhage resolution occurred at less than 4 months from onset and consequently PRP was completed. Vitreous hemorrhage differs with bleeding in other tissues due to the presence of vitreous collagen matrix which promotes rapid clotting and hinders resolution of hemorrhage by preventing passive diffusion and delay in inflammatory cellular response. The prognosis for clearing hemorrhage was better when the fundus reflex was brighter and the retina adjacent to the ora serrata was visible. Clearing occurred sooner when hemorrhage was retrohyaloid rather than in the vitreous gel. In diabetic eye, the vitreous undergoes metabolic derangements resulting in premature liquefaction and abnormal vitreoretinal adhesion leading to traction and membrane formation. Partial PVD has also been associated with higher rate of diabetic retinopathy progression since it serves as scaffold for growth of neovascular tufts.
Keywords: Resolving Vitreous Hemorrhage